(untitled) (Sinología hispánica. China Studies Review, 2024)
Throughout sixty years of development, the history of Chinese education in Romania has roughly experienced four stages: the embryonic stage (before 1956), the slow development stage (1956-2005), the rapid development stage (2006-2016), and the in-depth development stage (since 2017). Based on reviewing its development history, this paper provides important information concerning the most significant events, institutions, sinologists, textbooks, and monographs about Chinese education in different periods. From a diachronic perspective, sinology research in Romania on the one hand and language services and policy support from China on the other hand are two crucial factors that have contributed to the development of Chinese language education in Romania; from a synchronic perspective, Romanian Chinese education has built a complete talent training system for undergraduate, master, and Ph.D. However, the development of various universities is uneven; the Confucius Institute is the leading force in Chinese education in primary and secondary schools. The learners of Chinese are of different ages, and the evolution trend focuses on the young ones. The development trend of Chinese education in the new era should focus on localization.